2021
DOI: 10.1038/s41598-021-01541-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of molar-incisor hypomineralization: a systematic review and meta-analysis

Abstract: Molar-Incisor Hypomineralization (MIH) is a qualitative defect of enamel of unknown etiology, affecting one or more permanent molars and may include incisors. This condition is a clinical challenge and its prevalence is still uncertain given the recent increase in research. Thus, we aimed to comprehensively estimate the overall prevalence of MIH and associated characteristics. This systematic review is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 119 publications
4
35
1
13
Order By: Relevance
“…Most of the included studies reported no significant difference of prevalence between two genders [ 18 , 20 , 21 , 23 , 25 , 27 – 30 , 32 ] which in in accordance with the results reported by other systematic reviews [ 11 , 33 ]. However, two reported that MIH was more prevalent in girls [ 19 , 24 ] which can be attributed to the difference in time of eruption between two genders [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most of the included studies reported no significant difference of prevalence between two genders [ 18 , 20 , 21 , 23 , 25 , 27 – 30 , 32 ] which in in accordance with the results reported by other systematic reviews [ 11 , 33 ]. However, two reported that MIH was more prevalent in girls [ 19 , 24 ] which can be attributed to the difference in time of eruption between two genders [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…A previous systematic review in 2018, estimated a 14.2% global prevalence of MIH, with the highest and lowest prevalence in South America (18.0%) and Africa (10.9%) respectively [ 10 ]. A more recent meta-analysis published in 2021, reported a pooled prevalence of 13.5%, with the highest and lowest prevalence in American (15.3%) and Asian (10.7%) continents [ 11 ]. Other studies have even reported prevalence as low as 2.7% (Egypt) [ 12 ] to up to 19.7% (Brazil) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the latest estimated MIH global prevalence of 13.5% [ 4 ], the cross-country variety may range from 2.8 to 40.2% [ 21 ]. The prevalence of MIH in Portugal has never been estimated, therefore we used the worldwide estimated result of 13.5%, yet 32.7% of the participants believe that this may range between 5 and 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, MIH is an increasingly common dental defect in clinical practice. Globally, its estimated worldwide prevalence is 13.5%, with affected incisors in 36.6% of the cases [ 4 ], and about 27.4% of cases require therapeutic interventions [ 5 ]. Clinically, MIH is characterized by the translucency of enamel with a white, yellow to brownish coloration depending on severity [ 3 , 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NOS was used for assessing the risk of bias in clinical trials because their baseline assessments were considered in this meta-analysis. According to the obtained NOS scores, case–control studies were classified into three levels: low quality (0–4 points), medium quality (5–6) and high quality (7–9 points) and cross sectional studies were classified into four levels: unsatisfactory (0–4 points), satisfactory (5–6 points), good (7–8 points) and very good (9–10 points) (as previously performed 61 , 62 ). Any discrepancies were addressed by discussion to reach a consensus.…”
Section: Methodsmentioning
confidence: 99%